Um artefato para execução da estratégia em uma empresa varejista - Voos, Jerri Sidnei (Universidade do Vale do Rio dos Sinos, 2017)
The execution of the strategy still contemplates one of the main challenges in organizations - especially retailers - because the sales points are distant from the matrix and also by the constant changes that affect the way the customer consumes. This reality of the sector generates the need for a great organizational alignment, once the execution occurs far from the administrative center, which makes difficult the present identification of gap's that may occur. The complexity in executing the strategy is mainly due to the fact that it is not possible to promote a corporate strategy through a person or department, that is, a successful execution consists of a great organizational alignment. In this perspective, the present work had as objective to propose an artifact: by artifact is understood the organization of internal resources to reach external objectives. In this proposal, the artifact is composed of structural levers and processes, which aim to contribute to increase the chances of success in executing the strategy. To do so, we started with the following problem: what structural aspects and processes can contribute to increase the chances of success in the execution of the strategy? The research was a retailer company. In this environment, interviews were applied to the director, supervisors, logistics manager and commercial managers. As a result of this stage, the company's current structure and processes related to the execution of the strategy were identified, identifying the gap between the recommendations of the literature and the diagnosed reality. With this information, a customized artifact - a systemic cycle - was developed to execute the strategy, considering the recommendations of the literature and the reality of the company, aiming at overcoming the gap detected in the business environment.
Keywords: Estratégia; Execução da estratégia; Modelos de execução; Artefato de execução; Strategy; Strategy execution; Execution models; Execution artifact; ACCNPQ::Ciências Sociais Aplicadas::Administração